THE SHARIA BANK STABILITY: HOW FINTECH AND FINANCIAL RATIO FIXED IT? - Ailsa Nabila Az Zahra; Titis Miranti (I-Finance Journal, 2023)
This study aims to see whether the stability of Islamic banks is sufficiently dependent on financial technology and several financial ratios. The research was conducted at Islamic banks in Indonesia and Malaysia. To get the research sample used, a purposive sampling technique. The research sample consisted of 14 Islamic banks and was observed from 2017 to 2021. The analytical method uses panel data regression. The research results show. Capital Adequacy Ratio, Non-Performing financing (NPF), Equity-to-Assets Ratio (EAR) and firm size significantly affect bank stability, while financial technology, Assets Turnover, and Cost to Income Ratio (CIR) have no significant effect. Bank stability is one of the determinants of the goodness of state finances, so it needs to be a concern. Banks can increase capital values and firm size, then maintain NPF and EAR values to keep bank financial stability. Even though several other factors are not significant, banks still need to maintain the stability of their value so that the impact does not get worse.